1969
DOI: 10.1136/hrt.31.6.711
|View full text |Cite
|
Sign up to set email alerts
|

Acute haemodynamic effects of frusemide in patients with normal and raised left atrial pressures.

Abstract: Frusemide is a well-established diuretic (Vorburger, 1964;McKenzie, Fairley, and Baird, 1966;Kirkendall and Stein, 1968), and a mild hypotensive when given in a dosage of over 120 mg. daily (Davidov, Kakaviatos, and Finnerty, 1967). It is commonly used in the treatment of acute pulmonary oedema with beneficial results (Stason et al., 1966;Peltola, 1965;Biagi and Bapat, 1967 Though some work has been done-on the systemic haemodynamic effects of frusemide (International Furosemide Symposium, Bad Homburg, 1963),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 11 publications
3
13
0
1
Order By: Relevance
“…Lal et al (1) found no significant change in Ppa or Pla after furosemide in human patients with an initial Pla less than 10 torr; when Pla was above 10 torr however, furosemide caused a significant decrease in Ppa and Pla. Decreases of Ppa and Pla were small and inconsistent in our base-line experiments, perhaps because these were normal lambs; the changes were more evident in lambs with pulmonary edema from circulatory overload.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lal et al (1) found no significant change in Ppa or Pla after furosemide in human patients with an initial Pla less than 10 torr; when Pla was above 10 torr however, furosemide caused a significant decrease in Ppa and Pla. Decreases of Ppa and Pla were small and inconsistent in our base-line experiments, perhaps because these were normal lambs; the changes were more evident in lambs with pulmonary edema from circulatory overload.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have attributed its benefits to reduced plasma volume and pulmonary vascular pressures that result from diuresis (1)(2)(3)(4). Others have suggested that patients with pulmonary edema derive rapid improvement from furosemide even before diuresis, because of an extrarenal site of action (5-7), possibly related to changes in pulmonary blood volume.…”
Section: Introductionmentioning
confidence: 99%
“…Their effectiveness is attributable to the reduced filling pressure of the left heart and pulmonary capillaries, which results when central blood volume is reduced by diuresis and by the diuretic enhanced capacitance of the systemic venous bed (1)(2)(3)(4)(5)(6). Conceivably, such other mechaReceived for publication 11 May 1979 and in revised form 29 June 1979. 1494 nisms as increased plasma oncotic pressure or increased pulmonary lymph flow also reduce the pulmonary edema.…”
Section: Introductionmentioning
confidence: 99%
“…While bumetanide is known to produce increases in renal blood flow (Bollerup et al, 1974), the acute effects on left ventricular filling pressure and venous capacitance are less well defined and unlike other diuretics (Lal et al, 1969;Dikshit et al, 1973;Ramirez & Abelmann, 1968) bumetanide is associated with a decrease in total peripheral systemic resistance (Ziacchi et al, 1981).…”
Section: Introductionmentioning
confidence: 99%